Penyelesaian Tindak Pidana Fidusia Melalui Pendekatan Restorave Justice - Iwan Riswandie (Al-Adl : Jurnal Hukum, 2022)
Criminal acts are usually resolved through a procedural mechanism through the principle of legality with what is outlined through the provisions of the legislation. Restorative justice will be able to solve criminal problems which are not only seen in procedural settlement with an orientation towards punishment but also in the agreement of the parties. Criminal problems related to fiduciary with the criminal provisions of Articles 35 and 36 of the Fiduciary Act must see and be oriented to restorative justice to be able to solve the problem. This paper examines the Settlement of Fiduciary Crimes through a restorative justice approach. The method used is normative legal research with a statutory approach and a conceptual approach. In conclusion, restorative justice is prioritized not the punishment for the offender, but on how the perpetrator can bear responsibility for the acts committed and how the victim can get justice so that the situation can be recovered. Therefore, the main thing in the settlement of fiduciary crimes is the restoration of the original state, then with the emphasis on criminal law, of course, the debtor as the offender of the violation has the impetus for resolving this case, so that with this agreement with a strong pressure value in criminal law, the opportunity for settlements will be more achievable and far more beneficial than just punishing the offender.